10 % Dextrose and neonatal pain during venipuncture, regional Hospital Hermilio Valdizan of Huanuco, 2018 - Tarazona-Herrera, Karen Georgina (2020)
Objective. To determine the eﬀectiveness of oral administration of 10 % dextrose in neonatal pain during venipuncture at Regional Hospital Hermilio Valdizán of Huánuco, 2018. Methods. Quantitative, quasi-experimental, cross-sectional, prospective, analytical and comparative study. Two groups were analyzed of 103 neonates each, with intentional non-random sampling. In the case of the group of Neonatal Intensive Care Unit A area, 10 % dextrose was administered 2 minutes before venipuncture. While the control group in the Neonatal Intensive Care Unit B area received nothing. Pain was identifed one minute after venipuncture with the Neonatal Infant Pain Scale. Results. In the frst group, the absence of pain (67.00%) and mild pain (30.10 %) predominated. In the control group, moderate pain (39.81%) and intense pain (41.75%) prevailed; being statistically signifcant (p = 0.000); when comparing the same as the signifcant intervening variables. In consequence, the neonatal period (p = 0,000), post prandial time (time after food intake)(p = 0,000), gestational age (x2 = 61,2929.617 and x2 = 50,085, p = 0,000), antecedent of venipuncture (p = 0,000), sex (p = 0,000 ), evidenced the eﬀectiveness of dextrose at 10 %. Conclusion. The 10 % solution used was eﬀective in neonatal pain, regardless of the intervening variables studied.